2017
DOI: 10.1016/j.stem.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Myeloid Cells Regulate Myeloid-Biased Hematopoietic Stem Cells via a Histamine-Dependent Feedback Loop

Abstract: SUMMARY Myeloid-biased hematopoietic stem cells (MB-HSCs) play critical roles in recovery from injury, but little is known about how they are regulated within the bone marrow niche. Here, we describe an auto/paracrine physiologic circuit that controls quiescence of MB-HSCs and hematopoietic progenitors marked by histidine decarboxylase (Hdc). Committed Hdc+ myeloid cells lie in close anatomical proximity to MB-HSCs and produce histamine, which activates the H2 receptor on MB-HSCs to promote their quiescence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 49 publications
7
93
0
Order By: Relevance
“…HDC‐expressing myeloid cells are the dominant cells in the bone marrow and maintain a high level of histamine in the bone marrow cavity (Figure A,B), suggesting that all the haematopoietic stem cells (HSCs) are immersed in a histamine‐rich environment. Histamine deficiency in HSCs niche results in the loss of HSCs quiescence and enhanced myeloid proliferation . Consistent with previous observations, we found that histamine deficiency activates long‐term HSCs (LT‐HSCs, identified as CD48 − CD150 + Lin − Sca‐1 + C‐kit + [LSK]) and short‐term HSCs (ST‐HSCs, CD48 + CD150 + LSK) to quickly enter differentiation cycle, resulting in a significant increase in multipotent progenitors (MPPs, CD48 + CD150 − LSK) in response to infarct‐related myeloid demand (Figure C,D).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…HDC‐expressing myeloid cells are the dominant cells in the bone marrow and maintain a high level of histamine in the bone marrow cavity (Figure A,B), suggesting that all the haematopoietic stem cells (HSCs) are immersed in a histamine‐rich environment. Histamine deficiency in HSCs niche results in the loss of HSCs quiescence and enhanced myeloid proliferation . Consistent with previous observations, we found that histamine deficiency activates long‐term HSCs (LT‐HSCs, identified as CD48 − CD150 + Lin − Sca‐1 + C‐kit + [LSK]) and short‐term HSCs (ST‐HSCs, CD48 + CD150 + LSK) to quickly enter differentiation cycle, resulting in a significant increase in multipotent progenitors (MPPs, CD48 + CD150 − LSK) in response to infarct‐related myeloid demand (Figure C,D).…”
Section: Resultssupporting
confidence: 90%
“…Having uncovered that histamine deficiency results in platelet and neutrophil dysfunction and enhances neutrophil‐platelet interactions in vitro, we investigated whether histamine deficiency influences neutrophil‐platelet interactions and thrombosis in vivo. Platelets isolated from WT or HDC −/− donor mice were labelled with DiD and then injected through the tail vein into HDC‐EGFP mice, in which most neutrophils and fractional monocytes express EGFP . Intravital microscopy was performed in a model of FeCl 3 ‐induced endothelial injury of the mesenteric arterioles (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…HSC purified from mice lacking the histamine receptor H 2 R also showed engraftment defects after transplantation. These results thus strongly suggest that myeloid cells regulate myeloid-biased HSC directly via histamine-H 2 R signaling [38••]. …”
Section: Structure and Components Of The Hsc Nichementioning
confidence: 96%
“…When aged neutrophils infiltrate the BM, they are homeostatically cleared by BM macrophages via phagocytosis, thereby activating the macrophages and ultimately triggering CXCL12 reduction and HSC egress from the BM [37]. A recent report showed that histamine production is restricted to myeloid cells in the bone marrow (including some myeloid biased HSC) and that these myeloid-biased HSC associated specifically with Gr1 + myeloid cells (likely neutrophils) [38••]. Mice incapable of producing histamine showed reduced HSC quiescence and HSC purified from these mice showed impaired potential to reconstitute myeloid cells [38••].…”
Section: Structure and Components Of The Hsc Nichementioning
confidence: 99%
See 1 more Smart Citation